Rectal cancer—state of art of laparoscopic versus open surgery - Milone, Marco; Manigrasso, Michele; Burati, Morena (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (September 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
Since its introduction, laparoscopy has gained more and more consent in colorectal surgery, even if its role in rectal cancer surgery is still controversial and widely debated. The aim of this study is to present the ongoing situation of laparoscopic surgery for rectal cancer by a review of current literature. We performed a systematic search in the electronic databases (PubMed, Web of Science, Scopus, EMBASE) according to preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. We limited the search until 31 March 2017 and used the following search terms in all possible combinations: rectal cancer, laparoscopy, minimally invasive and open surgery. A total of 66 articles were include in this review, of which 38 were non-randomized trials, 8 were randomized controlled trials (RCTs) performed in a single center, 5 were multicentric RCTs and 15 were meta-analyses. Laparoscopic approach resulted in a faster and better recovery after surgery and has been proven to be equivalent in terms of short-terms outcomes comparing to the open approach. Nevertheless, the findings concerning oncologic safety of minimally invasive approach are still controversial. This should give the rationale to perform new meta-analyses based on the last evi-dences produced. Moreover, even more multicentric RCTs studies, hypothetically designed on new pathological outcomes, should be performed to finally assess if laparoscopy is a valid choice for the treatment of rectal cancer.